2019
DOI: 10.1128/aem.01107-19
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Adaptation Strategies in Salmonella enterica Serovar Enteritidis Revealed by Global Proteomic and Mutagenic Analyses

Abstract: Salmonella enterica subsp. enterica serovar Enteritidis is able to adapt to sublethal concentrations of ethanol, which subsequently induce tolerance of this pathogen to normally lethal ethanol challenges. This work aims to elucidate the underlying ethanol adaptation mechanisms of S. Enteritidis by proteomic and mutagenic analyses. The global proteomic response of S. Enteritidis to ethanol adaptation (5% ethanol for 1 h) was determined by isobaric tags for relative and absolute quantification (iTRAQ), and it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…45-, and 1.83-fold increase in survival) of cells, especially for ethanol stress (7.24-fold increase in survival under 10% ethanol for 2.5 h) (Figure 1). Similar results preformed in A. acidoterrestris and Salmonella enterica were also reported by the researchers that an increase in survival under thermal stress (65 • C, 5 min) from 14.72 to 62.09% in A. acidoterrestris or an improvement of ethanol tolerance (26.39fold increase in survival under 15% ethanol, 1 h) for S. enterica was observed through cross protection (He et al, 2019;Zhao et al, 2021). These results indicated that heat preadaptation may be considered as a potential strategy to engineer the robustness of strains used during food fermentation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…45-, and 1.83-fold increase in survival) of cells, especially for ethanol stress (7.24-fold increase in survival under 10% ethanol for 2.5 h) (Figure 1). Similar results preformed in A. acidoterrestris and Salmonella enterica were also reported by the researchers that an increase in survival under thermal stress (65 • C, 5 min) from 14.72 to 62.09% in A. acidoterrestris or an improvement of ethanol tolerance (26.39fold increase in survival under 15% ethanol, 1 h) for S. enterica was observed through cross protection (He et al, 2019;Zhao et al, 2021). These results indicated that heat preadaptation may be considered as a potential strategy to engineer the robustness of strains used during food fermentation.…”
Section: Discussionsupporting
confidence: 88%
“…Genetic information processing was essential to the growth and proliferation of lactic acid bacteria. For instance, the process of translation and DNA replication were indispensable for microbes to transmit genomic information (He et al, 2019;Yao et al, 2019). He et al (2019) reported that the upregulation of ribosome-related proteins contributed to improving the stress resistance of S. enterica under high ethanol conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific and technical advancements throughout the food chain (e.g., from agriculture and food manufacturing to preparation in the home) are critical to ensure microbial food safety. In the past two decades, microbial food safety research in China was initiated on many important aspects, such as rapid detection methods and devices, food control measures, antibiotic resistance mechanisms, stress response strategies, biofilm formation mechanisms, sublethal injury mechanisms, and microbial risk assessment (Shi and Zhu, 2009;He et al, 2019;Xie et al, 2019;Ling et al, 2020;Shen et al, 2020;Sheng et al, 2020). Research progress in the aforementioned aspects has contributed a lot to the improvement of microbial food safety in China, and these areas should thus be further explored as the focuses in the future.…”
Section: Future Research Directions In Microbial Food Safetymentioning
confidence: 99%
“…By means of the 2-DE technique, Yeh (2012) found that a total of 16 proteins were differentially expressed after exposure of C. sakazakii to 5% ethanol for 60 min. Moreover, the same sublethal ethanol treatment resulted in the differential expression of 138 proteins belonging to metabolism, enterobactin biosynthesis, virulence, and other pathways in S. Enteritidis ( He et al, 2019 ). To our best knowledge, however, there is no available literature on elucidating the ETR mechanisms in pathogenic bacteria at the transcriptome level.…”
Section: Introductionmentioning
confidence: 99%